"I Can't Crack the Code": What Suicide Notes Teach Us about Experiences with Mental Illness and Mental Health Care. (February 2019) - Furqan, Zainab; Sinyor, Mark; Schaffer, Ayal; Kurdyak, Paul; Zaheer, Juveria
Objective: While mental illness is a risk factor for suicidal behaviour and many suicide decedents receive mental health care prior to death, there is a comparative lack of research that explores their experiences of mental illness and care. Suicide notes offer unique insight into these subjective experiences. Our study explores the following questions: "How are mental illness and mental health care experienced by suicide decedents who leave suicide notes?" and "What role do these experiences play in their paths to suicide?" Method: We used a constructivist grounded theory framework to select a focus of qualitative analysis and engage in line-by-line open coding, axial coding, and theorizing of the data. Our sample is a set of 36 suicide notes that explicitly make mention of mental illness and/or mental health care, purposefully selected from a larger sample of 252 notes. Results: The primary themes from our sample were 1) negotiating personal agency in the context of mental illness, 2) conflict between self and illness, and 3) experiences of mental health treatment leading to hopelessness and self-blame. These experiences with mental illness and mental health care can give rise to exhaustion and a desire to exercise personal agency, contributing to suicidal behaviour. Conclusions and Relevance: This study highlights unique perspectives by suicide decedents, whose voices and experiences may not have been heard otherwise, addressing a critical deficit in existing literature. These insights can potentially enrich clinical care or strengthen existing suicide prevention programs.